2013
DOI: 10.1177/0361684313505844
|View full text |Cite
|
Sign up to set email alerts
|

Social Antecedents and Consequences of Gender-Sport Stereotypes During Adolescence

Abstract: Eccles' Expectancy-Value Model (Fredricks & Eccles, 2004) posits that the stereotypes endorsed by parents may influence their children's participation in leisure-time activities. This influence is presumed to occur through the mediating role of children's perceived competence and value given to the activity, predicting in turn dropout. Previous research is scarce relative to (a) the parent-child transmission of gender stereotypes and (b) the relationships among stereotypes, selfperceptions, and decision to dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
1
23
0
4
Order By: Relevance
“…In accordance to this, some authors (Boiché et al, 2014;Sheridan et al, 2014) consider that social factors are very important in dropout and sport abandonment, and it may have been its trigger. Finally, regarding autonomy, as previously mentioned, some authors have emphasized the benefits of feeling more autonomous within the sport context (Chen and Wu, 2016;Cheon et al, 2015;Reynolds and McDonough, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…In accordance to this, some authors (Boiché et al, 2014;Sheridan et al, 2014) consider that social factors are very important in dropout and sport abandonment, and it may have been its trigger. Finally, regarding autonomy, as previously mentioned, some authors have emphasized the benefits of feeling more autonomous within the sport context (Chen and Wu, 2016;Cheon et al, 2015;Reynolds and McDonough, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…This shows that both men and women with more favorable attitudes toward fencing club participation were more likely to continuously participate in the clubs. Boiché and colleagues [ 44 ] showed that gender stereotypes could affect people’s perceptions and behaviors with regard to sports or dance participation. It has been suggested that men tend to prefer activities that require more physical movements and are strenuous and competitive [ 45 ], but in comparison, women prefer sports that require fewer physical movements and expose themselves to less competitions with others [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile Viciana et al (2016) found that the Spanish adolescents accumulated just 4.4% of the daily MVPA these contexts as opportunities to compete, while girls might view them as opportunities to socialize with friends, especially in the unstructured contexts such as SR (Blatchford, Baines, & Pellegrini, 2003). A lower motivation toward PA in girls than in boys (Martínez-Baena & Mayorga-Vega, 2014) or gender-sport stereotypes (Boiche, Plaza, Chalabaev, Guillet-Descas, & Sarrazin, 2014) could also explain these differences.…”
Section: Discussionmentioning
confidence: 99%